Perbandingan GreenKonstitusi, GreenEkonomi, dan Hukum Ekonomi Syariah di Indonesia - Mohamad Nur Yasin (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2016)
The  rejection  of  unjustice  exploitation  to  natural environment  is  central  theme  of  green  constitution,  green  economic, and  sharia  economic  law.  The  problems,  how  do  comparison of essence and implementation between one and others. In  this paper is used study method in law normative. There are two important findings. First, the similarity of essence of green constitution, greeneconomic, and sharia economic law is focus on environment justice (eco-justice). The  differences,  environment  justice  under  perspective  of  (a)  green constitution  means  natural  environment  has  to  be  welfare  of  people, (b) green economic means natural environment is part of production, distribution,  and  ethical  consumption,  and  (c)  sharia  economic  law means  give  the  right  for  future  generations  to  enjoy  natural environment. Second, the similarity of implementation challenge faced by  three  concepts  is  inconsistention  of  law.  The  differences, inconsistention of law faced by (a) green constitution isinconsistension of environments Act with 1945 Constitution, (b) green economic is the loss  of  unlawfull  meaning  of  lawful  term  (c)  sharia  economic law  is systemic disobedience by sharia corporation to sharia principles.